Polyvictimization and psychosocial outcomes among trauma-exposed, clinic-referred youth involved in the juvenile justice system - Pane Seifert, Heather T. (Child maltreatment, 2022)
Polyvictimization is a robust predictor of emotional and behavioral problems and is linked to involvement in juvenile justice and other public sector systems. This study extends prior research by employing person-centered methods for identifying polyvictimization patterns among trauma-exposed, clinic-referred, justice-involved youth (n = 689; ages 12?18 years) and how identified classes differ on psychosocial outcomes and demographic characteristics. Most participants had experienced multiple traumatic event (TE) types. Latent class analyses identified three classes: mixed trauma/bereavement exposure group (55.1%; Mean = 3.0 TE types); maltreatment polyvictimized group (29.3%; Mean = 5.7 TE types); and maltreatment plus extreme violence polyvictimized group (15.7%; Mean = 9.3 TE types). Polyvictimized youth were more likely to be female, in out-of-home placements, and experiencing negative psychosocial outcomes (e.g., Posttraumatic Stress Disorder). Hispanic/Latino youth were overrepresented in the extreme polyvictimized subgroup. Results underscore the need for cross-system coordination of trauma-informed, comprehensive services for clinic-referred, justice-involved youth.